Relations among Executive Function, Decoding, and Reading Comprehension: An Investigation of Sex Differences. Issue 1 (2nd January 2021) - Spencer, Mercedes; Cutting, Laurie E.
ABSTRACT: In the current investigation, we used structural equation mediation modeling to examine the relations between executive function (indexed by measures of working memory, shifting, and inhibition), decoding ability, and reading comprehension in a sample of 298 children aged 6 to 8 years (132 boys and 166 girls). Results indicated that executive function was mediated by decoding ability. When sex was examined as a moderator of these associations, a trend suggested that direct relations between executive function and reading comprehension were stronger for girls compared with boys; no significant differences were found for other direct and indirect relations. Taken together, these findings highlight the importance of executive function in supporting underlying integrative processes associated with reading comprehension and emphasize the need to further consider the role of executive function in relation to reading.